Midodareni Transformation in Jawa Tondano: Cultural Adaptation and Islamic Integration - Makka, Misbahul Munir; Djafar, Moh. Ali Akbar; Hasan, Faradila; Kolopita, Abdul Fajri (Potret Pemikiran, 2024)
Customs in every place often experience changes because they are flexible. Activities, habits, and religion that impact good or bad moral values can change what occurs. Researchers identify the occurrence of cultural change midodareni; in addition, researchers get the problem of these changes by looking at the side of Islamic law. The research was conducted in Jawa Tondano (Jaton), North Sulawesi Province, with a sociological approach and the concept of sari. Data was collected by interviewing religious leaders and traditional community leaders. The analysis carries out using theory tradition. The findings are that midodareni became one of the traditions that experienced significant changes. This change influences factors of marriage, ethnicity/tribe immigrants who incidentally are the majority of Muslims in the sense that there is the influence of religion, namely Islam, so that the tradition is readjusted so as not to eliminate ancestral heritage and does not conflict with beliefs. In terms of analysis, the practice includes traditional authentic or changes allowed in Islamic teachings; midodareni is one example of a form of development of Islam that adapt to existing rules. So that this custom can be an innovation against other traditions where customary changes if they meet the moral values the local community believes.